Producción, agronomía y usos culinarios del Amaranthus spp. de Tochimilco, Puebla, México - Reyes Ramos, Yareli (2024)
Amaranth is a food with important nutritional and culinary properties, but its human consumption is limited due to the lack of dissemination about its use and gastronomic benefits. The objective of this work was to expose the origin, properties, benefits, and culinary uses of amaranth in Tochimilco, Puebla, to understand one of the limitations that this pseudocereal might have and relate it to its current consumption in that population, where it is cultivated and commercialized in addition to the City of Puebla. This article used a mixed methodology that included in-depth interviews with amaranth-producing families in the municipality of Tochimilco and a questionnaire applied to 390 potential consumers in that municipality and in the City of Puebla. The results were statistically analyzed through bivariate relationships, using SPSS v.20 software. The study results showed that 82.3% of the respondents are willing to consume more amaranth products due to their nutritional benefits. However, it was found that there is currently no plan to disseminate its culinary use in the City of Puebla or Tochimilco. Contribution and originality: This article highlights the importance, origin, properties, benefits, and culinary uses of amaranth in Tochimilco and the City of Puebla, emphasizing the need to disseminate its use and benefits to increase its human consumption. The mixed methodology used in this study provides a clearer view of the problem and its possible causes.